Development and Characterization of Crackers Substitution of Wheat Flour With Jellyfish - Maisont, Suchada; Samutsri, Wisutthana; Phae-ngam, Wuttichai; Limsuwan, Pichet (Frontiers in Nutrition, 2021)
The objective of this study was to investigate the possibility of using jellyfish (Lobonema smithii) for the production of nutritionally improved crackers. In this study, ground jellyfish were incorporated into different levels (20, 30, and 40%) to replace wheat flour in cracker formula. Physicochemical characteristics (linear expansion, hardness, and color) and sensory quality of the developed crackers were examined and compared with control crackers. The crackers with jellyfish were found significantly darker, with more brittleness, and less consumer accepted than the control samples (p < 0.05). Moisture content, aw, and thiobarbituric acid reactive substances (TBARS)-values of jellyfish crackers increased while the hardness of the jellyfish crackers decreased with increasing the storage time for both crackers stored at 35 and 45°C. The substitution of wheat flour with jellyfish led to high protein content in the crackers. The cracker with 30% of jellyfish gained characteristics of cracker, liking scores, as well as the subjective quality of the final product and had good physical and chemical conditions, being able to be consumed for 12 weeks stored at 35°C.